Integrating Traditional South Sulawesi Songs and Cuisine in English Language Teaching: A Cultural Approach to Language Learning - Rahmawati, Sitti; Ahdan, Ahdan; Fuad, Fawwas Roihan; Arham, Muhammad (Pascasarjana Universitas Negeri Makassar, 2024)
This study explores the integration of traditional South Sulawesi song lyrics and cuisine into English language teaching and tourism promotion, aiming to enhance cultural awareness, language proficiency, and regional identity. Through a qualitative descriptive approach, five traditional songs and an array of traditional dishes from South Sulawesi were analyzed to determine their potential as educational and promotional tools. The findings reveal that these cultural elements serve as rich, contextually relevant resources that not only enrich language learning by providing authentic materials for vocabulary acquisition and cultural competence but also strengthen tourism marketing by highlighting the unique cultural and culinary heritage of the region. The novelty of this study lies in its interdisciplinary approach, bridging language education and tourism to create a unified strategy for cultural preservation and economic development. The study addresses a gap in the literature by focusing on non-Western cultural content, particularly the rich traditions of South Sulawesi, offering a model for integrating local cultural elements into educational curricula and tourism strategies. The study concludes that traditional South Sulawesi song lyrics and cuisine can significantly enhance the educational experience for language learners while simultaneously promoting the region as a cultural and culinary destination. These findings suggest that a more integrated approach to cultural content in both language education and tourism can yield substantial benefits, fostering deeper connections between learners, tourists, and the cultural heritage of the region.